Percepção da síncope em palavras proparoxítonas - Lima, Giselly de Oliveira (2017)
The present study investigates the perception of the post-stressed vowels in proparoxytone words. The post-stressed vowels, our subject of study, may manifest in words of an antepenultimate stress variably in three ways: preserved, reduced or syncopated. Thus, when these are preserved or reduced, there are strategies offered by the language that do not support deletion of the vowel. In addition, the variation can be active allowing the performance of another strategy, implying the sacrifice of the vowel. In the literature, many studies on proparoxytones have investigated the production of these words, leaving a gap in how they are perceived. Thus, this research has as main objective to investigate the perception of the non-final post-stressed vowels in words with penultimate stress. The corpus was composed of 24 participants, 12 females and 12 males, aged from 15 to 50 years old, who were born in Rio Verde and Santa Helena de Goiás, both cities in the southwestern microregion of Goiás State, Brazil. The informants participated in two perception tests: one AX type discrimination test and one ABX type test. The results were statistically analyzed using the IBM SPSS software, version 20.0. The statistical analysis showed that the perception of words with non-final poststressed vowels was more accurate than the perception of the words with syncopated vowel. As for the phonological analysis of word perception, developed in the light of the presuppositions of the Model of the Interplay of Speech Perception and Phonology (Hume and Johnson, 2001), this allowed to verify that the informants tend to perceive the presence of the vowel, even in environments with the vowel syncopated. The data revealed that the external forces of perception, production, generalization and conformity act in neutralization, deletion or preservation of the post-stressed mid vowel. These forces function as filters in the selection of possible outputs. Furthermore, the perception filter can influence the phonological system, avoiding visible alterations. For this, it presents two aspects: perceptual salience and communicational environment. In cases where the listener perceives the word without syncope as being similar to the word with such a phenomenon, we argue that the perceptual salience between the syncopated and preserved proparoxytone words is low. We conclude, then, that the cognitive representation of proparoxytones is with the vowel. This can undergo changes, which pass through the filtering of external forces, generating different representations in the linguistic sound system of a community of speakers.